Analysis of SMAD4 Gene Promoter Methylation in Pancreatic and Endometrial Cancers - Nikolić, Aleksandra; Opinćal, Filip; Ristanović, Momčilo; Trifunović, Jovanka; Knežević, Srbislav; Radojković, Dragica (Archive of Oncology, 2018)
Background. Promoter hypermethylation of the SMAD4 gene has been registered in some cancer types, but in general doesn’t appear to be a frequent event in carcinogenesis. However, only a few published studies deal with this topic and not many cancer types have been analyzed. The aim of this study was to establish SMAD4 gene promoter methylation status in pancreatic and endometrial cancers. Methods. Patients included in the study (62 subjects) were diagnosed and surgically treated at the Clinical Center of Serbia, University of Belgrade. Patients with pancreatic carcinoma (17 subjects) underwent surgical removal of the pancreatic adenocarcinoma at the First Surgical Clinic, while the patients with endometrial carcinoma (45 subjects) underwent hysterectomy with adnexectomy at the Institute for Gynecology and Obstetrics. Extraction of DNA from fresh tissue samples was performed and the methylation status of the SMAD4 gene promoter was studied by a previously designed PCR-based HpaII and MspI restriction enzyme assay. The resulting PCR products were analyzed by electrophoresis in 2% agarose gels. Results. Neither of the analyzed samples was found to be hypermethylated. Conclusion. This is the first report on SMAD4 methylation status in pancreatic and endometrial tumor specimens, and supports the viewpoint that SMAD4 hypermethylation is not a common event in malignant tumors. Nevertheless, promoter hypermethylation remains a candidate mechanism for SMAD4 inactivation in malignant tissue as a potential cause of decreased or lost SMAD4 expression in certain tumor types, and should be further investigated in different tumor types and larger cohorts of patients.
Keywords: endometrial cancer; pancreatic cancer; Methylation